Optimized synthesis of biphasic calcium phosphate: enhancing bone regeneration with a tailored β-tricalcium phosphate/ hydroxyapatite ratio - Tran, Dieu Linh; Hoai Ta, Qui Thanh; Tran, Manh Hoang; Nguyen, Thi My Huyen; Le, Ngoc Thuy Trang; Hong, Anh Phuong Nguyen; Park, Hyun Ji; Park, Ki Dong; Nguyen, Dai Hai (Biomaterials Science, 2025)
Biphasic calcium phosphate (BCP) is a bioceramic widely used in hard tissue engineering for bone replacement. BCP consists of β-tricalcium phosphate (β-TCP) – a highly soluble and resorbable phase – and hydroxyapatite (HA) – a highly stable phase, creating a balance between solubility and resorption, optimally supporting cell interactions and tissue growth. The β-TCP/HA ratio significantly affects the resorption, solubility, and cellular response, with a higher β-TCP ratio increasing resorption due to its solubility. BCP is commonly synthesized by calcining calcium-deficient apatite (CDA) at temperatures above 700 °C via direct or indirect methods. This study investigated the effects of pH and sintering temperature on BCP synthesized via wet precipitation, aiming to achieve an 80/20 β-TCP/HA ratio, which is known to be optimal for bone regeneration. By maintaining a constant Ca/P precursor ratio of 1.533, the optimal conditions were determined to be a pH of 5.5–6 and a sintering temperature of 900 °C, chosen to balance material stability and solubility. The successful synthesis was confirmed using X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. At the same time, the material’s physical and chemical properties were further characterized through scanning electron microscopy (SEM) and degradation studies in a simulated body fluid (SBF). In vitro tests demonstrated excellent cytocompatibility and osteogenic differentiation, while in vivo studies on rabbit femur defects demonstrated significant bone regeneration, with bone-to-tissue volume ratios exceeding 50% within four weeks. These results highlight the potential of BCPs in bone tissue engineering and biomaterials research.
Keywords: Biphasic calcium phosphates; Bone regeneration; Bone replacement; Hard tissues; Optimized synthesis; Phosphate hydroxyapatite; Sintering temperatures; Synthesised; Tissues engineerings; Tri-calcium phosphates; Animals; Biocompatible Materials; Bone Regeneration; Bone Substitutes; Calcium Phosphates; Durapatite; Hydrogen-Ion Concentration; Hydroxyapatites; Rabbits; Temperature; Tissue Engineering